Tensile, rheological properties, thermal stability, and morphology of ethylene vinyl acetate copolymer/silica nanocomposites using EVA-g-maleic anhydride. (February 2014) - Hoang, Thai; Truc, Trinh Anh; Thanh, Dinh Thi Mai; Chinh, Nguyen Thuy; Tham, Do Quang; Trang, Nguyen Thi Thu; Vu Giang, Nguyen; Lam, Vu Dinh
In this article, we present a study on the properties of ethylene vinyl acetate copolymer/silica nanocomposites prepared in absence and presence of EVA-g-maleic anhydride as a compatibilizer between silica nanoparticles and ethylene vinyl acetate matrix. A series of ethylene vinyl acetate/silica nanocomposites with different contents of silica nanoparticles were prepared by solution method. EVA-g-maleic anhydride with 0.5 wt% maleic anhydride groups was added to all ethylene vinyl acetate/silica nanocomposites. Fourier transform infrared, field emission scanning electron microscopy, rheology behavior, and thermogravimetry analysis were used to characterize the structure, morphology, rheological, and thermal properties of the nanocomposites, respectively. The Fourier transform infrared spectra and field emission scanning electron microscopy micrographs showed that the hydroxyl groups on the surface of silica nanoparticles interact with maleic anhydride groups in EVA-g-maleic anhydride and lead to a finer dispersion of individual silica nanoparticles in the ethylene vinyl acetate matrix. The rheological properties and thermal stability of ethylene vinyl acetate/silica nanocomposites were significantly increased after adding EVA-g-maleic anhydride into the nanocomposites. Mechanical properties including tensile strength and elongation at break of the nanocomposites were mainly affected by the content of silica nanoparticles. For the tensile strength as well as elongation at break of the nanocomposites, a maximum value was observed at the content of 0.5 wt% of silica nanoparticles. The addition of EVA-g-maleic anhydride into ethylene vinyl acetate/silica nanocomposites resulted in a further improvement of mechanical properties of the nanocomposites.